Analysis of Lead (Pb) Levels in Mojokerto, East Java Province - Mohammad Yusuf Alamudi; Henry Sudianto; Dhonna Anggraeni; Sri Wardini; Putri Lestari; Sari Priyanti; Sulis Diana; Elyana Mafticha; Eka Diah Kartiningrum; Arief Fardiansyah (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Lead (Pb) is a heavy metal that is carcinogenic and takes a long time to decompose. Heavy metals in the environment can enter the human body through the food chain. Objective : The aim of this study is to analyze Lead (Pb) levels in the Mojokerto environment, East Java Province. Research Methods/ Implementation Methods : The method used was a literature study through a Google search engine search using the keywords lead (Pb) and Mojokerto, followed by analysis using Vosviewer Results : From the results of the research conducted, lead heavy metals were found in humans (hair and nails), aquatic plants, soil and fish. In addition, based on Vosviewer, it was found that the majority were carried out in 2022. Conclusion/Lesson Learned : Further research is needed to update data on lead levels in biotic and abiotic environments.